Some Properties of a Generalized Integral Operator - Yalçın, S.; Swamy, S. R.; Magesh, N.; Nirmala, J. (Communications in Mathematics and Applications, 2021)
The object of the present paper is to derive some properties of holomorphic functions in the open unit disc which are defined by using a new generalized integral operator by applying a lemma due to Miller and Mocanu. Also we mention some interesting consequences of our main results.
Keywords: Holomorphic function; dierential subordination; generalized integral operator.